Simultaneous conversion of methane and methanol into gasoline over bifunctional Ga-, Zn-, In-, and/or Mo-modified ZSM-5 zeolites - Choudhary, Vasant R.; Mondal, Kartick C.; Mulla, Shafeek Abdul Rashid (Angewandte Chemie-International Edition, 2005)
Keywords: gallium; heterogeneuos catalysis; methane activation; Molybdenum; zeolites

Solvent-free selective oxidation of benzyl alcohol by molecular oxygen over uranium oxide supported nano-gold catalyst for the production of chlorine-free benzaldehyde - Choudhary, Vasant R.; Jha, Rani; Jana, Prabhas (Green Chemistry, 2007)
A detailed investigation on the production of chlorine-free benzaldehyde in the solvent-free oxidation of benzyl alcohol by O-2 over nano-gold supported on U3O8 has been carried out. Influence of different catalyst parameters (different methods of gold deposition on U3O8, gold loading and particle size, and catalyst calcination temperature) and reaction conditions (reaction period and temperature) on the process performance has been studied. The catalyst containing gold at higher concentration and with smaller gold particles showed the better process performance (higher benzyl alcohol conversion and benzaldehyde yield or selectivity). The benzyl alcohol conversion is largely increased but the selectivity for benzaldehyde is slightly decreased (while that of benzyl benzoate is increased) with increasing the reaction period or temperature. In the presence of solvent (viz. tolune, p-xylene, DMF or DMSO), the process performance was found to be inferior to that observed in the absence of any solvent. Substituted benzyl alcohols also can be oxidized by O-2 to corresponding aldehydes with high yield and/or selectivity, using the catalyst in the absence of any solvent.

Supported copper oxide as a highly active/selective catalyst for the epoxidation of styrene by TBHP to styrene oxide - Choudhary, Vasant R.; Jha, Rani; Chaudhari, Nitin K.; Jana, Prabhas (Catalysis Communications, 2007)
Liquid phase epoxidation of styrene by anhydrous and aqueous TBHP to styrene oxide has been studied under reflux, using different supported CuO (viz. Cuo/Si-MCM-41, CuO/Al2O3, CuO/Ga2O3 and CuO/In2O3) as easily separable and reusable heterogeneous catalysts. The CuO/Ga2O3 catalyst showed the best performance in the epoxidation by aqueous TBHP. The CuO supported on In2O3 or Si-MCM-41 also showed very good performance in the epoxidation but only by anhydrous TBHP. However, the CUO/SiO2 catalyst, however, showed very good performance in the epoxidation by both the anhydrous and aqueous TBHP. Influence of the reaction conditions (temperature, time and TBHP/styrene ratio) on the epoxidation by aqueous TBHP over the best catalyst (CuO/Ga2O3) has been investigated. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: CuO/Al2O3; CuO/Ga2O3; CuO/In2O3; Cuo/Si-MCM-41; CuO/SiO2; epoxidation; styrene; Styrene oxide; tertiary butyl hydroperoxide

Synergetic effect of two halogen promoters present in acidic reaction medium or catalyst on the H2O2 formation (in H-2-to-H2O2 oxidation) and destruction over Pd/C (or Al2O3) catalyst - Choudhary, Vasant R.; Jana, Prabhas (Journal of Catalysis, 2007)
A strong synergetic effect of two different halide anions (F- and I-, Cl- and I-, Cl- and Br-, and F- and Br-) at optimum concentration in the catalyst or in an acidic reaction medium was observed in the H-2-to-H2O2 oxidation over Pd/C, Pd/Al2O3, and halogenated Pd/Al2O3 catalysts. The synergetic effect promote, the net H2O2 formation by inhibiting the H2O2 decomposition and hydrogenation reactions. The effect is most pronounced for the combination of fluoride (or chloride) and iodide anions. The Br (1 wt%)-F (1 wt%)-Pd (5 wt%)/Al2O3 catalyst showed very high H2O2 yield (59%)/selectivity (60%) in the H-2-to-H2O2 oxidation. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: H-2-to-H2O2 oxidation; H2O2 decomposition H2O2 hydrogenation; halogen promoter; Hydrogen peroxide; Pd/Al2O3; Pd/C; synergetic effect

Selective epoxidation of styrene to styrene oxide by TBHP using simple transition metal oxides (NiO, CoO or MoO3) as highly active environmentally-friendly catalyst - Choudhary, Vasant R.; Jha, Rani; Jana, Prabhas (Catalysis Communications, 2008)
Simple transition metal oxides, such as NiO, CoO or MoO3, etc. show high catalytic activity for the selective epoxidation of styrene to styrene oxide by TBHP. The order of choice for different transition metal oxides for epoxidation is NiO > CoO > MoO3 > Cr2O3 > Fe2O3 > ZnO >= U3O8 >> TiO2 >> MnO2. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: CoO; epoxidation; MoO3; NiO; styrene; Styrene oxide; TBHP

Synthesis of substituted styrenes and stilbenes mediated by palladium on zirconia - Borate, Hanumant B.; Dumbre, Deepa K.; Wakharkar, Radhika D.; Choudhary, Vasant R. (Journal of Chemical Research-S, 2008)
Palladium on zirconia has been found to be an effective catalyst for the synthesis of various substituted styrenes and stilbenes, including biologically active natural products, by reaction of aryl halides with olefins.
Keywords: heterogeneous catalyst; palladium on zirconia; stilbenes; styrenes

Supported nano-gold catalysts for epoxidation of styrene and oxidation of benzyl alcohol to benzaldehyde - Choudhary, Vasant R.; Dumbre, Deepa K. (Topics in Catalysis, 2009)
Nano-gold particles supported on different alkaline earth oxides (viz. MgO, CaO, BaO and SrO), Gr. IIIa metal oxides (viz. Al(2)O(3), Ga(2)O(3), In(2)O(3) and Tl(2)O(3)), transition metal oxides (viz. TiO(2), Cr(2)O(3), MnO(2), Fe(2)O(3), CoO(x), NiO, CuO, ZnO, Y(2)O(3) and ZrO(2)), rare earth metal oxides (viz. La(2)O(3), Ce(2)O(3), Nd(2)O(3), Sm(2)O(3), Eu(2)O(3), Tb(2)O(3), Er(2)O(3) and Yb(2)O(3)) and U(3)O(8) [all prepared by depositing gold on corresponding metal oxide support by deposition precipitation (DP) and/or homogeneous deposition precipitation (HDP) method] were evaluated for their catalytic performance in the liquid phase epoxidation of styrene by tert-butyl hydroperoxide (TBHP) to styrene oxide and also in the solvent-free benzyl alcohol-to-benzaldehyde oxidation (by molecular oxygen or TBHP) reactions. For the epoxidation, the catalytic performance (styrene oxide yield) of the most promising nano-gold catalysts prepared by the HDP method was in the following order: Au/MgO > Au/Tl(2)O(3) > Au/Yb(2)O(3) > Au/Tb(2)O(3) > Au/CaO (or TiO(2)). However, for the oxidation of benzyl alcohol to benzaldehyde by molecular oxygen, the order of choice for the most promising catalysts (based on benzaldehyde yield) was Au/U(3)O(8) > Au/Al(2)O(3) > Au/ZrO(2) > Au/MgO. Whereas, when TBHP was used as an oxidizing agent for the benzyl alcohol oxidation, the order of choice for the most promising catalysts was Au/U(3)O(8) > Au/MgO > Au/TiO(2) > Au/ZrO(2) > Au/Al(2)O(3). The catalytic performance of a particular supported nano-gold catalyst was thus found to depend on the reaction catalysed by them. Moreover, it is strongly influenced by a number of catalyst parameters, such as the metal oxide support, the method of gold depositon on the support, the gold loading and also on the catalyst calcination temperature. Nano-gold particles-support interactions seem to play an important role in controlling the deposition of gold ( amount of gold deposited and size and morphology of gold particles), formation of different surface gold species (Au(0), Au(1+) and Au(3+)) and electronic properties of gold particles and, consequently, control the catalytic performance (both the activity and selectivity) of the supported nano-gold catalysts in the reactions. The nano-gold catalysts prepared by the HDP method showed much better catalytic performance than those prepared by the DP, coprecipitation or impregnation method; in general, the HDP method provided supported gold catalysts with much higher gold loading and/or smaller size gold particles than that achieved by the DP and other methods.
Keywords: Benzaldehyde; Benzyl alcohol; epoxidation; Metal oxide supports; Nano-gold catalysts; Oxidation; styrene; Styrene oxide

Solvent-free selective oxidation of benzyl alcohol to benzaldehyde by tert-butyl hydroperoxide over U3O8-supported nano-gold catalysts - Choudhary, Vasant R.; Dumbre, Deepa K. (Applied Catalysis A-General, 2010)
Liquid-phase oxidation of benzyl alcohol to benzaldehyde by tertiary butyl hydroperoxide over different uranium oxide supported nano-gold catalysts in the absence of a solvent has been thoroughly investigated. The influences of catalyst parameters [viz, method of gold deposition (impregnation, co-precipitation, deposition-precipitation and homogeneous deposition-precipitation), gold loading (08 wt%) and catalyst calcination temperature (100-900 degrees C)] on the catalyst performance have been investigated. The influence of reaction conditions [viz, reaction time (0-2 h) and temperature (25-94 degrees C)] on the process performance has also been studied. The Au/U3O8 catalyst prepared by the homogeneous deposition-precipitation and calcined at 400 degrees C showed very high activity (100% benzyl alcohol conversion with >85% selectivity for benzaldehyde) in the process for a short reaction period (0.5 h) at 94 degrees C. The catalyst also showed excellent reusability in the process. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Au/U3O8 catalyst; Benzaldehyde; Benzyl alcohol; Nano-gold; Partial oxidation; tert-Butyl hydroperoxide

Solvent-free selective oxidation of primary alcohols-to-aldehydes and aldehydes-to-carboxylic acids by molecular oxygen over MgO-supported nano-gold catalyst - Choudhary, Vasant R.; Dumbre, Deepa K. (Catalysis Communications, 2011)
Magnesium oxide supported nano-gold catalyst (prepared by the homogeneous deposition precipitation technique) showed high activity/selectivity and excellent reusability in the oxidation of different primary alcohols and aldehydes to corresponding aldehydes and carboxylic acids, respectively, by molecular oxygen (under atmospheric pressure) in the absence of any solvent. Influence of the catalyst calcination temperature (400-900 degrees C), reaction temperature (50-120 degrees C) and use of different solvents (viz. toluene. p-xylene, DMF or DMSO) on the oxidation reaction has also been studied. (C) 2011 Published by Elsevier B.V.
Keywords: Alcohols; aldehydes; Au/MgO; Molecular oxygen; Solvent-free oxidation

Solvent-free one-pot synthesis of sulfonephthaleins from saccharin and phenols - Tillu, V. H.; Dumbre, Deepa K.; Borate, Hanumant B.; Wakharkar, R. D.; Choudhary, Vasant R. (Synthetic Communications, 2012)
Sulfonephthaleins can be synthesized in a single pot from saccharin and phenol via the in situ formation of 2-sulfobenzoic anhydride, followed by its reaction with phenol using H2SO4 as the condensing agent, in the absence of any solvent. This solvent-free synthesis is more economical and environmentally benign.
Keywords: H2SO4; Phenols; saccharin; sulfonephthalein

Solvent-free oxidation of aldehydes to acids by TBHP using environmental-friendly -exchanged Mg-Al hydrotalcite catalyst - Choudhary, Vasant R.; Dumbre, Deepa K.; Narkhede, Vijay S. (Journal of Chemical Sciences, 2012)
A number of hydrotalcite (Mg-Al, Mn-Al, Co-Al, Ni-Al, Mg-Fe, Mg-Cr and Cu-Al) catalysts, with or without MnO-exchange, were evaluated for their performance in the solvent-free oxidation of benzaldehyde to benzoic acid by tert-butyl hydroperoxide under reflux in the absence of any solvent. The MnO-exchanged Mg-Al-hydrotalcite (Mg/Al = 10) showed high activity in the oxidation of different aromatic and aliphatic aldehydes to their corresponding acids and also showed excellent reusability in the oxidation process which is environmental-friendly.
Keywords: acid; Aldehyde; MnO4-1-exchanged Mg-Al-hydrotalcite catalyst; Oxidation; TBHP

Suzuki-Miyaura cross-coupling reaction between aryl halides and phenylboronic acids over gold nano-particles supported on MgO (or CaO) and other metal oxides - Dumbre, Deepa K.; Yadav, P. N.; Bhargava, Suresh Kumar; Choudhary, Vasant R. (Journal of Catalysis, 2013)
Gold nano-particles-supported alkaline earth metal oxides, particularly MgO or CaO, show high catalytic activity in the Suzuki-Miyaura cross-coupling reaction in the presence of K2CO3 and DMF (as a solvent). The catalytic activity is strongly influenced by the nature or type of metal oxide support (viz, alkaline earth oxide, Group IIIA metal oxide, transition metal oxide, or rare earth oxide actinide oxide). It is also strongly influenced by the nature of aryl halide (aryl iodide, bromide, chloride, or fluoride), amount of K2CO3 in the reaction mixture and catalyst calcination temperature. Influence of reaction parameters viz, temperature and time and different substituents in aryl halides and/or phenylboronic acids on the biphenyl product yield in the reaction over Au/MgO catalyst has also been investigated. The catalyst showed excellent reusability in the reaction. Moreover, it is ligand-free and also has much lower cost than the commonly used homogeneous and heterogeneous Pd catalysts. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Aryl halides; Au/MgO (or CaO) catalyst; Biphenyls; Gold nano-particles; phenylboronic acids; Suzuki-Miyaura coupling reaction